Probing the internal rotation of pre-white dwarf stars with asteroseismology: the case of PG 0122+200 - Corsico, Alejandro Hugo (2011)
We put asteroseismological constraints on the internal rotation profile of the GW Vir (PG1159-type) star PG 0122+200. To this end we employ a state-of-the-art asteroseismological model for this star and assess the expected frequency splittings induced by rotation adopting a forward approach in which we compare the theoretical frequency separations with the observed ones assuming different types of plausible internal rotation profiles. We also employ two asteroseismological inversion methods for the inversion of the rotation profile of PG 0122+200. We find evidence for differential rotation in this star. We demonstrate that the frequency splittings of the rotational multiplets exhibited by PG 0122+200 are compatible with a rotation profile in which the central regions are spinning about 2.4 times faster than the stellar surface.